FEATURES OF ENTREPRENEURIAL ACTIVITY IN THE HOSPITALITY INDUSTRY - Мазуркевич, Ірина; Онищук, Наталя (SWorldJournal, 2025)
The study analyzes diverse definitions of "entrepreneurship" from leading Ukrainian scholars and distinguishes it from the broader concept of "business," highlighting the formalized and legally defined nature of entrepreneurship in Ukraine.